Study of Price and Its Effects on Cosmetic Products (Voice: A Biannual & Bilingual Journal, 2023)
This article explores the vibrant cosmetics industry in Nepal, where a wide range of national and international brands serve a clientele that is becoming more discriminating and fashion-conscious. Due to increased emphasis on personal hygiene and appearance as well as a growing middle class, Nepal's cosmetics sector has grown significantly. Nepal's cosmetic market has a wide variety of brands, with most products coming from Europe, China, Singapore, Thailand, India, and the United Arab Emirates. The study looks at how customers' opinions and behaviors about cosmetic items are influenced by age, income, occupation, marital status, and education. It shows that quality, brand awareness, and value for money are highly preferred by consumers in the area. But the survey also shows that a certain customer sector is becoming more and more interested in herbal and natural cosmetics. According to the research, there are potential for marketers in Kohalpur, Nepal's cosmetic business to customize their approaches in order to better meet the diverse preferences and demands of their target audience. Understanding consumer attitudes and behavior is essential for product positioning, pricing, and promotional activities as the cosmetics business in Nepal develops further. According to the research, there are potential for marketers in Kohalpur, Nepal's cosmetic business to customize their approaches in order to better meet the diverse preferences and demands of their target audience. Understanding consumer attitudes and behavior is essential for product positioning, pricing, and promotional activities as the cosmetics business in Nepal develops further.